Free vibration of functionally graded sandwich plates with stiffeners based on the third-order shear deformation theory - Pham Tien Dat; Do Van Thom; Doan Trac Luat (Vietnam Journal of Mechanics)
In this paper, the free vibration of functionally  sandwich grades plates with stiffeners is investigated by using the finite  element method. The material properties are assumed to be graded in the  thickness direction by a power-law distribution. Based on the third-order  shear deformation theory, the governing equations of motion are derived from  the Hamilton's principle. A parametric study is carried out to highlight the  effect of material distribution, stiffener parameters on the free  vibration characteristics of the plates.